FAKTOR DETERMINAN KEPATUHAN MEMBAYAR IURAN JKN PADA PESERTA MANDIRI DI KOTA MALANG - Anak Agung Istri Citra Dewiyani; Rizki Fadila (Politeknik Kesehatan Kemenkes Malang, 2022)
Background: JKN is the government's program to provide health insurance to all people di Indonesia which is held by BPJS Kesehatan. One of the problems faced by BPJS is deficit condition. In June 2020, the deficit at BPJS has reached Rp. 6.54 trillion. One of the causes of the deficit BPJS caused there to be many JKN participants who do not obey the rules for paying JKN contributions properly, especially participants from the PBPU segment. In August 2020, in Malang, JKN contributions that are not paid reached Rp. 50,700,898,326 and in Blimbing District are the highest arrears reached Rp. 11,276,087,156 Subjects and Method: This is a quantitative analytic study with a cross-sectional approach. Samples were taken by non-randomized sampling using quota sampling of 143 respondents. This study used univariate analysis, bivariate, and multivariate analysis to know the dominant factor that correlates to the dependent variable. Results: The results showed that determinant factors that correlate the compliance in paying JKN contribution are: knowledge factor (p-value: 0.001), perception (p-value: 0.046), distance (p-value: 0.022), and time (p-value: 0.044). Based on the multivariate test results, the dominant factor that correlates with compliance in paying JKN contribution is the knowledge factor (p-value: 0,000). Conclusion: From this study, a recommendation that can be given to BPJS is to held more events to increase JKN participants' knowledge about the JKN program. When JKN participant has the proper knowledge, we hope they have proper behaviour in paying JKN contribution properly. Keywords: JKN contribution; Compliance; Determinant Factors